P195 Syrian labour in lebanon: review of current trends in the literature. (1st September 2016) - Habib, Rima R
Abstract : Background: Since the 1960s, millions of Syrian migrants have worked in Lebanon's construction, agriculture, and service sectors. The advent of the Syrian Civil War that displaced about 1.5 million Syrians to Lebanon dramatically shifted the Lebanese labour market. Syrian migrant workers have always received low wages and experienced job insecurity, but the mass influx of refugees has exacerbated labour conditions, depressing wages and increasing exploitation. Healthcare access has also become increasingly problematic for Syrians, who before the war had access to universal healthcare in Syria, but now must pay out of pocket in Lebanon. Syrians must navigate these challenges while experiencing bigotry from an antagonistic Lebanese state and population. Methods: This research explores the work and health of Lebanon's Syrian migrant workers. The author will conduct a systematic review of scholarly and grey literature and news reports on the topic in English and Arabic. The search will be conducted using Academic Search Premier, Google Scholar, and Google News. The terms utilised in the search include 'Syrian refugee' 'Syrian worker' 'refugees in Lebanon' 'labour rights' and 'discrimination'. Identified texts will be read by the author and thematically coded (i.e., 'refugee, ' 'worker, ' 'exploitation, ' 'legal rights, ' 'discrimination, ' and 'occupational health'). The researcher will conduct a thematic analysis to synthesise cogent concepts relating to the work experiences of Syrians in Lebanon. Results: This report will identify the spectrum of Syrian work experiences in Lebanon, including workplace discrimination and exploitation and occupational health. Moreover, the paper will synthesise data on the life conditions of Syrian workers in the country. Discussion: The paper's analysis will argue for expanded programs protecting the health and wellbeing of Syrian workers and their families. Furthermore, the author will propose a research agenda that supports civil society organisations working to protect the livelihoods of Syrians in the country.